Preparing the teacher in the light of a future vision (Journal of the College of Basic Education, 2023)
The issue of (teacher preparation) began to receive unprecedented attention as it is no longer an educational matter.It was confined to those interested and specialized in teacher preparation only, but exceeded it to become an important matter.in general. The reality of teacher preparation, in its institutions and treaty, has become one of the most prominent issues.And the debate is according to the conference, studies and reports. (The Fifth Conference of Arab Educators,(1993) and the Eighth Conference of Arab Teachers (1996), (Future Determination: Changing the wayWe are promised by the teacher (Cooper, 1999), who strongly criticized the faculties of education in major universities.because of the teachers who did not receive solid academic degrees, which requires the need to re-Consider teacher preparation programs.